2022
DOI: 10.1111/cns.13917
|View full text |Cite
|
Sign up to set email alerts
|

Genetic spectrum of NOTCH3 and clinical phenotype of CADASIL patients in different populations

Abstract: Introduction:Cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a relatively common cerebral small vessel disease. NOTCH3 has been identified as the causative gene of CADASIL. Clinical variability and genetic heterogeneity were observed in CADASIL patients and need to be further clarified. Aims:The aim of the study was to clarify genetic spectrum of NOTCH3 and clinical phenotype of CADASIL patients. Methods: Suspected CADASIL patients were collected by our c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…In addition, most of our CADASIL patients presented with ischemic stroke or recurrent TIA and a few suffered from migraine, which was different from Caucasians due to the higher proportion of migraine in Caucasians. 40 Inherited metabolic disorders are common causes of child leukoencephalopathies, 41 but they were found not to be rare in our adult leukoencephalopathies cohort. Several metabolic disorders were identified that affected very long chain fatty acid profile (ALD), serum cholestanol/urinary bile alcohols (CTX), specific enzyme activities (PKU and Krabbe disease) and plasma amino acid profile (homocystinuria).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, most of our CADASIL patients presented with ischemic stroke or recurrent TIA and a few suffered from migraine, which was different from Caucasians due to the higher proportion of migraine in Caucasians. 40 Inherited metabolic disorders are common causes of child leukoencephalopathies, 41 but they were found not to be rare in our adult leukoencephalopathies cohort. Several metabolic disorders were identified that affected very long chain fatty acid profile (ALD), serum cholestanol/urinary bile alcohols (CTX), specific enzyme activities (PKU and Krabbe disease) and plasma amino acid profile (homocystinuria).…”
Section: Discussionmentioning
confidence: 66%
“…Some novel cysteine‐sparing mutations in NOTCH3 , such as p.R90H and p.V237M, were also found in our study. In addition, most of our CADASIL patients presented with ischemic stroke or recurrent TIA and a few suffered from migraine, which was different from Caucasians due to the higher proportion of migraine in Caucasians 40 …”
Section: Discussionmentioning
confidence: 91%
“…Among the symptomatic NOTCH3 R607C variant carriers, the prevalence of vascular risk factors was around one-third, but the relationship with stroke was not elaborated. 21 From a community-based perspective, our biobank study provides information on the cardiovascular risk factors impact on NOTCH3 variants in greater magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…The NOTCH3 variant landscape in the East Asian population was diverse, yet the NOTCH3 R544C variant (EGFr 13/14) and the NOTCH3 R607C variant (EGFr 15) top the most frequent variants. 21 In hospital-recruited studies of the NOTCH3 R544C carriers, sibling history of stroke and hypertension was related to intracerebral hemorrhage incidence. 9,22 Given the unavailable information on the NOTCH3 R544C carriers with hemorrhagic stroke in Taiwan Biobank, it may be suggested that further studies of the cohort are needed with vascular risk contributions to specific stroke types.…”
Section: Discussionmentioning
confidence: 99%
“…[1] NOTCH3 was identified as a pathogenic gene for CADASIL. [2] The NOTCH3 gene encodes a membrane-bound receptor protein, and to date, several different NOTCH3 gene mutations have been identified. [3] Here, we report a case of CADASIL with a heterozygous mutation c.931T > G (thymine > guanine) on the exon region of the NOTCH3 gene, resulting in an amino acid change p.C311G (cysteine > glycine).Case report: We report a case of a female patient with CADASIL whose genetic sequencing revealed a mutation in the NOTCH3 gene.…”
mentioning
confidence: 99%